1994
DOI: 10.1021/jo00091a019
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Diamines for a New Protocol To Determine the Enantiomeric Composition of Alcohols, Thiols, and Amines by 31P, 1H, 13C, and 19F NMR

Abstract: A new experimental protocol is described which greatly improves our recently reported method for the determination of the enantiomeric composition of alcohols, phenols, thiols, and amines. Thus, successive addition into the NMR tube of (1) a chiral fluorinated diamine (or any other chiral Cg symmetrical diamine), (2) CDCI3, (3) a tertiary amine, (4) PCI3, and 5) the chiral alcohol, phenol, thiol, or amine allows a 31P NMR spectrum of the diastereomeric derivatives to be recorded in 5 min. The method is accurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(39 citation statements)
references
References 1 publication
1
38
0
Order By: Relevance
“…Moreover, we also compared the outcomes obtained by the use of CDA 1 with the results determined by polarimetry (entries [12][13][14]. We found that they agreed well with each other.…”
Section: Determination Of the Enantiomeric Excess Of Chiral Alcohols supporting
confidence: 53%
See 1 more Smart Citation
“…Moreover, we also compared the outcomes obtained by the use of CDA 1 with the results determined by polarimetry (entries [12][13][14]. We found that they agreed well with each other.…”
Section: Determination Of the Enantiomeric Excess Of Chiral Alcohols supporting
confidence: 53%
“…Moreover, the value of δ (5.10-8.38 ppm) is larger than the ones obtained from the other chiral phosphorus derivatizing agents reported previously. For example when rac-␣-methylphenylmethanol was used as the substrate, the δ (6.88 ppm) was much larger than the results determined by use of other chiral phosphorus derivatizing agents [11][12][13][14], which ranged from 0.10 ppm to 1.40 ppm.…”
Section: Resultsmentioning
confidence: 67%
“…[ZnCl(C 8 H 16 N 2 ) 2 ] Cl À [ZnCl 2 (C 8 H 16 N 2 )] 2 (12): M r 969.9, m 2.11 mm À1 ; T min , T max 0.6732, 0.7366, d x 1.53g cm À3 , tetragonal, P4 1 2 1 2, Z 4, a 13.8279(6), c 22.0358(12) , U 4213.5(4) 3 . 52 049 measured reflections, 4110 unique reflections of which 3231 were observable j F o j> 4 s(F o )); R int for equivalent reflections 0.043.…”
Section: Methodsmentioning
confidence: 99%
“…This synthesis of (R,R)-2,2'-bipyrrolidine (9) could be carried out on a large scale (0.4 mol) in 61 % overall yield, starting from 6 and using only acid ± base wash purifications and a final distillation, with an ee value of > 99 % (the ee value was determined by 31 P NMR spectroscopy). [12] With (R,R)-2,2'-bipyrrolidine (9) in hand, we easily prepared the corresponding aminals 10 with several aldehydes, [13] by simple stirring of the diamine with the aldehyde, in diethyl ether at room temperature (Scheme 4). None of the reactions however, gave products suitable for X-ray crystallography.…”
mentioning
confidence: 99%
“…Besides the 31 P NMR spectra of the diasteroisomers 186, also 1 H, 13 C and 19 F spectra may be taken. Addition of sulfur or selenium to the NMR tube will afford diasteroisomers 187, for which the corresponding spectra can also be taken 397 NMR assignment of configuration served for development of a method claimed to be of great reliability for establishing the absolute configuration of amines with an asymmetric center in the˛position, for which no reference compound is needed. The first step consists of derivatizing the amine with a chiral reagent, for example N-[(S)-2-methoxy-2-phenylacetoxy]succinimide (188), as shown in reaction 33 for the methyl ester of (R)-tyrosine.…”
Section: Derivatizationmentioning
confidence: 99%